PENGARUH GIZI KURANG TERHADAP PENCAPAIAN PERKEMBANGAN ASPEK MOTORIK KASAR DAN MOTORIK HALUS PADA ANAK USIA 0-36 BULAN DI WILAYAH PUSKESMAS JATI KUDUS - Rusnoto Rusnoto; Noor Cholifah (Universitas Muhammadiyah Kudus, 2014)
Malnutrisi is circumstance patologis of arising out of effect of is lack of asupan energi protein and during a given time period. If child experience of less gizi, clear hence will be dangerous to continuity of child life , its problem is child stand in need of kecukupaan gizi to process growth and growth which exactly take place fast very in age batita. growth And growth represent health gizi parameter which sensitive enough to assess child health, especially the and batita baby child. This research aim to to know influence malnutrisi to harsh growth motorik attainment time accuracy and refine at age child 0-36 month;moon in Puskesmas Jati Kudus.Intake sampel Method in the non random sampling , old fellow bringing his child to posyandu ( specially the age child 0-36 month;moon) in Puskesmas Jati Kudus as sampel in this research. Mount malnutrisi measured by using criteria WHO-NCHS and mount child growth attainment time accuracy [in] measure by using kuisioner ( DDST) and KPSP. Research Location [in] Puskesmas Jati Kudus From result of enumeration indicate that value of X calculate 10,97 and assess X table 10,645 [at] harsh motorik and smooth motorik, hence interpretasinya is there influence of malnutrisi to accuracy of time attainment of harsh motorik [at] child of age 0-36 month;moon in Puskesmas Jati Kudus.Conclusion from this research expected by energy of health can improve of about gizi of his influence and child to growth and growth especially child of baby and batita. For the researcher is hereinafter expected more complete relevant research with this research, so that get better result.